Pricing Neighborhoods - Sadegh S. M. Eshaghnia; James J. Heckman; Goya Razavi (Institute of Labor Economics (IZA), 2023)
Education in Denmark is freely available. Despite near equal teacher salaries and per-pupil school expenditure across districts, there is substantial spatial heterogeneity in school quality as measured by teacher quality and student test scores. We argue that this is due to sorting of teachers and students across neighborhoods. We develop and apply multiple methods for identifying parental evaluations of measured school quality in the presence of strong neighborhood sorting. There is strong concordance in the estimates across diverse methodologies. We estimate a willingness to pay of about 3% more for a house with average characteristics when test scores are one standard deviation above the mean. Controlling for selection into neighborhoods only slightly reduces our estimates. Given that school quality, as measured by monetary resources, is equalized across all neighborhoods, payments for school quality embodied in housing prices are in fact payments for peer, teacher, and neighborhood quality. This evidence challenges the appropriateness of the current emphasis in the literature on Tiebout-based models of neighborhood choice that stress sorting on parental income in order to finance the local public good of school quality. Rather, a model of neighborhood choice to select neighbor and peer quality is more appropriate. Our evidence is consistent with evidence that cash expenditures on classrooms have weak effects on child achievement.
Keywords: H0; H4; H7; I2; R0; R2; R3; 330; hedonic valuation; amenities; residential sorting; peer effects